The bells of St. Mary's [videorecording (DVD)] - McCarey, Leo; Crosby, Bing, 1903-1977; Bergman, Ingrid, 1915-1982; Travers, Henry, 1874-1965; Gargan, William, 1905-1979; Donnelly, Ruth, 1896-1982 (Republic Pictures ; Distributed by Artisan Home Entertainment, 2003)
Easy-going Father O'Malley and iron-willed Sister Benedict find themselves in a subtle battle of wits over how the children should be educated at St. Mary's parochial school. Meanwhile, the skinflint businessman next door wants the school condemned.